Implementation of Assemblr Edu to Identify Farm Animals for Children with Intellectual Disabilities in SLB Tamima Mumtaz Pujon - Harahap, Ghesa Akbar; Choirunnisa, Hema Pramestika; Dewantoro, Dimas Arif (Journal of Education for Sustainability and Diversity, 2025)
This study aims to examine the implementation of the Assemblr Edu application based on augmented reality (AR) in introducing farm animals to students with disabilities at Tamima Mumtaz Special School (SLB). The research was conducted using quantitative methods through Pretest and post-test. Data were obtained through participatory observation, in-depth interviews with teachers, analysis of supporting documents, and learning media experiments. The results showed that the use of Assemblr Edu can increase the interest and understanding of deaf students on farm animal material. Visualization of animals in three-dimensional and interactive form helps students to more easily recognize and understand the characteristics of these animals. Teachers also reported an increase in student participation in teaching and learning activities as well as improved cognitive and fine motor skills. However, this study also found some obstacles, such as limited technology infrastructure in schools and the need for additional training for teachers. Overall, the implementation of Assemblr Edu in Tamima Mumtaz SLB shows great potential as an effective learning tool for students with disabilities, although it needs further adjustments and support to optimize the learning process.